Phenotypic and genotypic characterization of isoniazid resistance mutations in Mycobacterium tuberculosis isolates from new and previously treated patients in the Tshwane region - Maningi, Nontuthuko Excellent (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2020.